Extending the panel of inelastic scattering reactions availaible for dosimetry: Definition of the experimental campaign at the JSI TRIGA reactor - Grégoire Gilles; Radulovic Vladimir; Žerovnic Gasper; Domergue Christophe; Philibert Hervé; Fausser Clément; Tisseur David; Thiollay Nicolas; Barbot Loic; Destouches Christophe (EPJ Web of Conferences)
The epithermal to fast neutron domain lacks reactions to enhance the knowledge of spectrum in this energy range (1 keV to 1 MeV). Previous studies on this topic focused on 94Zr(n, γ) capture and 117Sn(n, n′) inelastic reactions. In the framework of a research collaboration between the French Atomic and Alternative Energies Commission (CEA) and the Jožef Stefan Institute (JSI), a new project consists in finding new inelastic reactions suitable for dosimetry. This paper describes the selection process of new reactions to be tested in an experimental campaign at JSI.